Composite material, molded product, and method of manufacturing molded product
Patent Information
- Application Number
- JP2023148329
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0006】 本発明により、リサイクル強化繊維等の強化繊維を用いても、しなやかさに優れた複合材料であって、機械的強度に優れた成形品を提供可能な複合材料、および、成形品を提供可能になった。
Smart Images

Figure 2025041188000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to composite materials, molded articles, and methods of making molded articles, and in particular to composite materials that include continuous thermoplastic fibers and continuous reinforcing fibers. [Background technology]
[0002] In recent years, fiber-reinforced resin composite materials in which thermoplastic resins are reinforced with continuous reinforcing fibers have been attracting attention. By using continuous reinforcing fibers, high mechanical properties can be expected, and by using thermoplastic resins, advantages such as secondary processability can be obtained. However, thermoplastic resin composite materials reinforced with continuous reinforcing fibers have a problem in that it is difficult to impregnate the continuous reinforcing fiber bundles with thermoplastic resin because the melt viscosity of the resin is high. In order to solve this problem, a mixed fiber yarn, which is a fibrous intermediate material in which continuous thermoplastic resin fibers and continuous reinforcing fibers are mixed, has attracted attention (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-098669 A [Patent Document 2] JP 2014-173196 A Summary of the Invention [Problem to be solved by the invention]
[0004] The above-mentioned blended yarn is a material with excellent flexibility. On the other hand, in recent years, it is expected that recycled reinforcing fibers will be used from the viewpoint of effective utilization of resources. Here, recycled reinforcing fibers are often collected by burning molded products of thermosetting resin reinforced with reinforcing fibers, but this burning often causes damage to the recycled reinforcing fibers. Fiber-reinforced resin materials using damaged reinforcing fibers tend to have poor mechanical strength when molded into products. In addition, it is difficult to manufacture a composite material with excellent flexibility while using reinforcing fibers recovered from molded products of thermosetting resin. The present invention aims to solve such problems, and to provide a composite material and a molded article that are excellent in flexibility even when using reinforcing fibers such as recycled reinforcing fibers, and that can provide molded articles with excellent mechanical strength. [Means for solving the problem]
[0005] In view of the above-mentioned problems, the present inventors have conducted studies and have found that the above-mentioned problems can be solved by using a predetermined ratio of a thermoplastic resin (3) having a lower melting point than the resin constituting the continuous thermoplastic resin fiber when binding the continuous thermoplastic resin fiber and the continuous reinforcing fiber having a thermosetting resin on the surface thereof. Specifically, the above problems were solved by the following means. <1> A composite material comprising continuous thermoplastic resin fibers (1), continuous reinforcing fibers (2) having a thermosetting resin on the surface thereof, and a thermoplastic resin (3) having a melting point lower than that of a resin constituting the continuous thermoplastic resin fibers (1), wherein the continuous reinforcing fibers (2) contain the thermosetting resin in a proportion of 2 to 40 mass%, the content of the thermoplastic resin (3) contained in the composite material is 5 to 80 parts by mass per 100 parts by mass of the total of the continuous thermoplastic resin fibers (1) and the thermoplastic resin (3), and at least a part of the continuous thermoplastic resin fibers (1) and at least a part of the continuous reinforcing fibers (2) are bound via the thermoplastic resin (3). <2> The continuous reinforcing fibers (2) include recycled continuous reinforcing fibers. <1> The composite material according to claim 1, <3> The continuous reinforcing fibers (2) include recycled continuous carbon fibers, <1> or <2> The composite material according to claim 1, <4> The continuous thermoplastic resin fiber (1) and the thermoplastic resin (3) each independently contain a polyamide resin. <1> ~ <3> 2. The composite material according to claim 1 , <5> The resin constituting the continuous thermoplastic resin fiber (1) contains a xylylenediamine-based polyamide resin containing diamine constituent units and dicarboxylic acid constituent units, and 70 mol % or more of the diamine constituent units are derived from xylylenediamine. <1> ~ <4> 2. The composite material according to claim 1 , <6> The thermoplastic resin (3) contains a xylylenediamine-based polyamide resin that contains diamine structural units and dicarboxylic acid structural units, and 70 mol % or more of the diamine structural units are derived from xylylenediamine. <1> ~ <5> 2. The composite material according to claim 1 , <7> 50 mol % or more of the dicarboxylic acid constituent units in the xylylenediamine-based polyamide resin are constituent units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. <5> or <6> The composite material according to claim 1, <8> a continuous thermoplastic resin fiber layer in which the continuous thermoplastic resin fibers (1) are arranged in parallel in one direction; The continuous reinforcing fibers (2) have a continuous reinforcing fiber layer arranged in parallel in one direction, The thermoplastic resin (3) binds the continuous thermoplastic resin fiber layer and the continuous reinforcing fiber layer. <1> ~ <7> 2. The composite material according to claim 1 , <9> The continuous thermoplastic resin fibers (1) and the continuous reinforcing fibers (2) are arranged in the same direction. <8> The composite material according to claim 1, <10> The continuous reinforcing fiber (2) is contained in an amount of 40 to 90 parts by mass relative to 100 parts by mass of the total of the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2). <1> ~ <9> 2. The composite material according to claim 1 , <11> It is in the form of a tape. <1> ~ <10> 2. The composite material according to claim 1 , <12> For Tailored Fiber Placement processing, <1> ~ <11> 2. The composite material according to claim 1 , <13> The continuous reinforcing fibers (2) are recycled carbon fibers, The continuous thermoplastic resin fiber (1) and the thermoplastic resin (3) each independently contain a diamine constituent unit and a dicarboxylic acid constituent unit, and the xylylenediamine-based polyamide resin contains 70 mol % or more of the diamine constituent units derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid constituent units in the xylylenediamine-based polyamide resin are derived from α,ω-linear aliphatic dicarboxylic acid constituent units having 4 to 20 carbon atoms. The continuous thermoplastic resin fiber (1) has a continuous thermoplastic resin fiber layer in which the continuous thermoplastic resin fibers (1) are arranged in one direction, and a continuous reinforcing fiber layer in which the continuous reinforcing fibers (2) are arranged in one direction, and the thermoplastic resin (3) binds the continuous thermoplastic resin fiber layer and the continuous reinforcing fiber layer, and the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2) are arranged in the same direction, and the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2) are arranged in the same direction, and the continuous reinforcing fiber layer contains 40 to 90 parts by mass of the continuous reinforcing fiber (2) per 100 parts by mass of the total of the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2), and is in the form of a tape. Placement) processing, <1> ~ <12> 2. The composite material according to claim 1 , <14> <1> ~ <13> A molded article formed from the composite material according to any one of claims 1 to 5. <15> For the base material, <1> ~ <13> A method for producing a molded article, comprising stitching the composite material described in any one of claims 1 to 4 to perform a tailored fiber placement process. Effect of the Invention
[0006] According to the present invention, it is possible to provide a composite material and a molded article which are excellent in mechanical strength and which are excellent in flexibility even when reinforcing fibers such as recycled reinforcing fibers are used. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the composite material of the present embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the composite material of the present embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing an example of the composite material of this embodiment subjected to TFP processing. [Figure 4] FIG. 4 is a photograph of the embroidery produced by TFP processing in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values are those at 23° C. unless otherwise specified.
[0009] In this specification, unless otherwise specified, the weight average molecular weight and the number average molecular weight are values calculated as polystyrene standards measured by GPC (gel permeation chromatography). In this specification, unless otherwise specified, the weight average molecular weight and the number average molecular weight can be measured according to the description in paragraph 0047 of JP2018-165298A, the contents of which are incorporated herein by reference. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated. The scale of Figures 1 to 3 may not be consistent with reality.
[0010] The composite material of the present embodiment is a composite material having continuous thermoplastic resin fibers (1), continuous reinforcing fibers (2) having a thermosetting resin on the surface thereof, and a thermoplastic resin (3) having a melting point lower than that of the resin constituting the continuous thermoplastic resin fibers (1), wherein the continuous reinforcing fibers (2) contain the thermosetting resin in a ratio of 2 to 40 mass%, the content of the thermoplastic resin (3) contained in the composite material is 5 to 80 parts by mass per 100 parts by mass of the total of the continuous thermoplastic resin fibers (1) and the thermoplastic resin (3), and at least a part of the continuous thermoplastic resin fibers (1) and at least a part of the continuous reinforcing fibers (2) are bound via the thermoplastic resin (3). By adopting such a configuration, it is possible to obtain a composite material that is excellent in flexibility and is capable of providing a molded product having excellent mechanical strength.
[0011] A known method for bonding thermoplastic resins and reinforcing fibers is to make prepregs by hot pressing. However, when molding products with many irregularities, a more flexible composite material than prepregs may be required. In this embodiment, the composite material is one containing continuous thermoplastic resin fibers (1) in which the thermoplastic resin maintains a fibrous shape. Specifically, the inventors have succeeded in producing a composite material with excellent flexibility by binding continuous thermoplastic resin fibers (1) and continuous reinforcing fibers (2) having a thermosetting resin on their surfaces via a thermoplastic resin (3) (sometimes referred to as a "binder resin" in this specification) having a lower melting point than the resin constituting the continuous thermoplastic resin fibers (1). Furthermore, by using a thermoplastic resin with a low melting point as the binder resin, it dissolves sufficiently during heat molding and does not remain as a foreign matter in the molded product. Furthermore, recycled reinforcing fibers can be used as the raw material for the composite material of this embodiment, so that it can be environmentally friendly. In the composite material of this embodiment, the continuous thermoplastic resin fibers (1) are preferably arranged with regularity. In the composite material of this embodiment, the continuous reinforcing fibers (2) are preferably arranged with regularity. Arranged with regularity includes fibers arranged in parallel in one direction (opened continuous reinforcing fiber roving), woven fibers, knitted fibers, etc. Needless to say, regularity in the present invention includes not only regularity in a geometric sense, but also normal errors in the technical field of the present invention. An example of an arrangement without regularity is nonwoven fabric.
[0012] FIG. 1 is a schematic diagram showing an example of the composite material of this embodiment, and is a cross-sectional view in a direction perpendicular to the longitudinal direction of the continuous reinforcing fiber (2). The composite material 10 shown in FIG. 1 is in the form of a tape. By forming it in the form of a tape, further processing becomes easier. Here, in FIG. 1, 1 indicates the continuous thermoplastic resin fiber (1), 22 indicates the part of the continuous reinforcing fiber itself among the continuous reinforcing fiber (2), 3 indicates a thermoplastic resin (3) (binder resin) having a lower melting point than the resin constituting the continuous thermoplastic resin fiber (1), and 4 indicates a thermosetting resin present on the surface of the continuous reinforcing fiber 22 among the continuous reinforcing fiber (2). That is, the continuous reinforcing fiber (2) in this specification means one including the continuous reinforcing fiber itself 22 and the thermosetting resin 4.
[0013] Returning to FIG. 1, the composite material 10 includes continuous thermoplastic resin fibers (1), continuous reinforcing fibers (2) having a thermosetting resin 4 on their surfaces, and a thermoplastic resin (3) having a melting point lower than that of the resin that constitutes the continuous thermoplastic resin fibers (1). By using the continuous reinforcing fiber itself 22 with a relatively large amount of the thermosetting resin 4 covering the surface thereof, damage to the reinforcing fiber can be minimized even when recycled reinforcing fiber is used. The thermosetting resin 4 may cover a part of the surface of the continuous reinforcing fiber itself 22, or may cover the entire surface of the continuous reinforcing fiber itself. It is preferable that the thermosetting resin 4 covers 50% or more of the surface area of the continuous reinforcing fiber itself 22, and more preferably covers 80% or more. The thermosetting resin 4 may cover 100% of the surface area of the continuous reinforcing fiber itself 22. The thermosetting resin 4 may contain resin additives, fillers, surface treatment agents for reinforcing fiber, and the like, in addition to the curable resin. These will be described in detail later.
[0014] In this embodiment, at least a part of the continuous thermoplastic resin fibers (1) and at least a part of the continuous reinforcing fibers (2) are bound together via a thermoplastic resin (3) (binder resin). In FIG. 1, almost all of the continuous reinforcing fibers (2) and almost all of the continuous thermoplastic resin fibers (1) are bonded together via a binder resin 3. In the composite material of this embodiment, the continuous reinforcing fibers (2) and the continuous thermoplastic resin fibers (1) are bound together using the binder resin 3, so that the continuous thermoplastic resin fibers (1) can be maintained in a fibrous state, and flexibility can be achieved for the resulting composite material.
[0015] In this embodiment, the binder resin 3 preferably covers 20% or more, and more preferably 40% or more, of the surface area of the continuous thermoplastic resin fiber (1). The binder resin 3 may cover 100% of the surface area of the continuous thermoplastic resin fiber 1, but even if it covers 15% or less, the required performance is sufficiently satisfied.
[0016] The shape of the composite material 10 of this embodiment is not particularly limited, but it is preferably in the form of a tape. When the composite material of the present embodiment is in the form of a tape, its thickness is preferably 100 μm or more, more preferably 20 μm or more. By making it equal to or more than the lower limit, the time required for making a preform (molding before heat processing) tends to be shortened. In addition, the thickness of the tape-shaped composite material is preferably 500 μm or less, more preferably 400 μm or less. By making it equal to or less than the upper limit, the resin can be impregnated into the reinforcing fibers, shortening the molding time, and the mechanical properties of the resulting molded product tend to be improved. When the composite material of the present embodiment is in the form of a tape, its width is preferably 5 mm or more, more preferably 8 mm or more. By making it equal to or more than the lower limit, the time required for making a preform using a TFP or a braid tends to be shortened. In addition, the width of the tape-shaped composite material is preferably 25 mm or less, more preferably 20 mm or less. By making it equal to or less than the upper limit, the design of the resulting molded product tends to be improved.
[0017] The composite material of the present embodiment preferably has a continuous thermoplastic resin fiber layer in which continuous thermoplastic resin fibers (1) are arranged in parallel in one direction, and a continuous reinforcing fiber layer in which the continuous reinforcing fibers (2) are arranged in parallel in one direction, and the thermoplastic resin (3) binds the continuous thermoplastic resin fiber layer and the continuous reinforcing fiber layer. The continuous thermoplastic resin fiber layer in which the continuous thermoplastic resin fibers (1) are arranged in parallel in one direction includes a layered shape in which the continuous thermoplastic resin fiber layers are arranged in a row, as shown in Fig. 1. Such a layered shape can be formed, for example, by opening a multifilament continuous thermoplastic resin fiber consisting of a plurality of continuous thermoplastic resin fibers. The continuous reinforcing fiber layer in which the continuous reinforcing fibers (2) are arranged in parallel in one direction includes a layered shape in which the continuous reinforcing fiber layers are arranged in a row, as shown in Fig. 1. Such a layered shape can be formed, for example, by opening a continuous reinforcing fiber bundle consisting of a plurality of continuous reinforcing fibers. In addition, recycled reinforcing fibers recovered from UD tapes (Uni-directional Tapes) can also be used. In the composite material of the present embodiment, the continuous thermoplastic resin fibers (1) and the continuous reinforcing fibers (2) are preferably arranged in parallel in the same direction.
[0018] Fig. 2 shows another example of the composite material of the present embodiment, in which the continuous thermoplastic resin fibers (1) and the continuous reinforcing fibers (2) are arranged in parallel in one direction, but the continuous thermoplastic resin fibers (1) and the continuous reinforcing fibers (2) are dispersed and mixed. The symbols are the same as those in Fig. 1.
[0019] In addition to the above, in the composite material of the present embodiment, it is also preferable that the woven fabric of the continuous thermoplastic resin fibers (1) and the woven fabric of the continuous reinforcing fibers (2) are bonded via the binder resin 3.
[0020] The composite material of the present embodiment may be used as is, but is usually preferably used for applications in which it is further processed (secondary processing). The composite material of the present embodiment may be directly heat-processed, but because of its flexibility, it is preferably used as a yarn for Tailored Fiber Placement (TFP) processing, or as a yarn for use in applications involving reeling, such as braiding machines, knitting machines, and weaving machines. Examples of applications involving reeling include braided cords and twisted cords.
[0021] FIG. 3 shows an example of the composite material of this embodiment subjected to TFP processing, in which 10 indicates the composite material of this embodiment and 11 indicates a thread. In the TFP processing, preferably, the composite material 10 is arranged so as to follow the shape of a molded article, and stitched with thread 11. The thread 11 is usually a continuous thermoplastic resin fiber. One preferred form of the thermoplastic resin fiber is a thermoplastic resin fiber corresponding to the continuous thermoplastic resin fiber (1), and another preferred form is a thermoplastic resin fiber formed from a resin constituting the binder resin 3. The composite material of this embodiment can be preferably used for a molded article having, for example, two or more, preferably three or more, folded parts as shown in FIG. 3. In particular, it can be preferably used for a molded article having a folded part with a folding angle of 90° or more as shown in FIG. 3.
[0022] <Continuous thermoplastic resin fiber (1)> Next, the continuous thermoplastic resin fiber (1) will be described. The continuous thermoplastic resin fiber (1) used in this embodiment refers to a thermoplastic resin fiber having a fiber length of more than 6 mm, preferably more than 12 mm, more preferably more than 30 mm, and even more preferably more than 10 cm. The average fiber length of the continuous thermoplastic resin fiber (1) used in this embodiment is not particularly limited, but from the viewpoint of improving molding processability, it is preferably 1 m or more, more preferably 100 m or more, even more preferably 1,000 m or more, and preferably 20,000 m or less, more preferably 1,0000 m or less, and even more preferably 7,000 m or less.
[0023] In the composite material of the present embodiment, the total fineness of the continuous thermoplastic resin fibers (1) is preferably 200 to 12000 dtex, and more preferably 1000 to 10000 dtex. By setting it in such a range, the effects of the present embodiment can be more effectively exhibited. The total number of the continuous thermoplastic resin fibers (1) in the composite material of the present embodiment is preferably 10 to 10,000 f, more preferably 100 to 5,000 f, and even more preferably 500 to 3,000 f. By setting it in such a range, a composite material having better physical properties and texture can be obtained.
[0024] The continuous thermoplastic resin fiber (1) used in the present embodiment is mainly composed of a thermoplastic resin (usually 90% by mass or more, preferably 95% by mass or more, and 100% by mass or less of 100% by mass is a thermoplastic resin). The continuous thermoplastic resin fiber (1) may also contain known additives, etc., as appropriate. The thermoplastic resin used for the continuous thermoplastic resin fibers (1) can be a wide variety of known thermoplastic resins, and is usually a crystalline resin. Specific examples of the thermoplastic resin used for the continuous thermoplastic resin fiber (1) include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyamide resin, polyethylene terephthalate and polybutylene terephthalate, polyether ketone resins such as polyoxymethylene resin, polyether ketone, polyether ether ketone, polyether ketone ketone and polyether ether ketone ketone, polyether sulfone resin, polyether sulfide resin, thermoplastic polyether imide, thermoplastic polyamide imide, wholly aromatic polyimide, semi-aromatic polyimide and other thermoplastic polyimide resins, and polyamide resin is more preferable. The polyamide resin used in this embodiment may be either an aliphatic polyamide resin or an aromatic polyamide resin. The aliphatic polyamide resin means a polyamide resin in which aromatic monomer-derived structural units account for less than 20 mol% of the total structural units constituting the polyamide resin. Examples of aliphatic polyamide resins include polyamide 4, polyamide 46, polyamide 6, polyamide 66, polyamide 666, polyamide 610, polyamide 11, polyamide 116, polyamide 12, polyamide 612, etc. The aromatic polyamide resin includes a diamine structural unit and a dicarboxylic acid structural unit, and 20 to 80 mol % (preferably 30 to 80 mol %, more preferably 40 to 70 mol %) of the total structural units of the diamine structural unit and the dicarboxylic acid structural unit is a structural unit containing an aromatic ring. By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained molded product can be increased. Examples of the semi-aromatic polyamide resin include polyamide 6T / 6I, polyamide 66 / 6T, polyamide 9T, polyamide 10T, and xylylenediamine-based polyamide resins described below, and xylylenediamine-based polyamide resins are preferred.
[0025] The xylylenediamine-based polyamide resin in this embodiment is a polyamide resin that contains a xylylenediamine-based polyamide resin that contains diamine constituent units and dicarboxylic acid constituent units, and in which 70 mol % or more of the diamine constituent units are derived from xylylenediamine. Preferably, the xylylenediamine-based polyamide resin has 50 mol % or more of the dicarboxylic acid constituent units derived from an α,ω-linear aliphatic dicarboxylic acid having a carbon number of 4 to 20. In the composite material of the present embodiment, the strength and chemical resistance inherent to the xylylenediamine-based polyamide resin can be exhibited.
[0026] The diamine constituent units of the xylylenediamine-based polyamide resin are preferably derived from xylylenediamine (preferably paraxylylenediamine and / or metaxylylenediamine, more preferably metaxylylenediamine) at 75 mol% or more, more preferably 80 mol% or more, even more preferably 85 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, and particularly preferably 99 mol% or more. The dicarboxylic acid constituent units of the xylylenediamine-based polyamide resin are preferably derived from α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms at 60 mol% or more, even more preferably 70 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, and particularly preferably 99 mol% or more.
[0027] In the present embodiment, the molar ratio of metaxylylenediamine and paraxylylenediamine in the xylylenediamine, when the total of metaxylylenediamine and paraxylylenediamine is 100 moles, is preferably metaxylylenediamine / paraxylylenediamine is 00-100 / 100-0, preferably 10-100 / 90-0, more preferably 20-100 / 80-0, even more preferably 50-90 / 50-10, and even more preferably 60-80 / 40-20. By including paraxylylenediamine, the melting point of the polyamide resin can be increased.
[0028] Diamines other than metaxylylenediamine and paraxylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, 1,3-bis( Examples of the diamines include alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.
[0029] As described above, the xylylenediamine-based polyamide resin preferably has at least 50 mol % of the dicarboxylic acid constituent units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. The carbon number of the α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms is preferably 6 or more, and is preferably 18 or less, more preferably 16 or less, even more preferably 14 or less, even more preferably 13 or less, and even more preferably 12 or less. Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are preferably used as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid. One or a mixture of two or more of these can be used. Among these, one or more of adipic acid, sebacic acid, and dodecanedioic acid are more preferred, and sebacic acid is more preferred. A preferred embodiment of the xylylenediamine-based polyamide resin in this embodiment is one in which 50 mol % or more (preferably 70 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid constituent units are derived from one or more of adipic acid, sebacic acid, and dodecanedioic acid (preferably sebacic acid).
[0030] Examples of dicarboxylic acid components other than the above-mentioned α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.
[0031] In addition, the xylylenediamine-based polyamide resin contains diamine structural units and dicarboxylic acid structural units as main components, but does not completely exclude other structural units, and may contain structural units derived from lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acids such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that the total number of diamine structural units and dicarboxylic acid structural units is the largest among all structural units among the structural units constituting the xylylenediamine-based polyamide resin. In this embodiment, the total of diamine structural units and dicarboxylic acid structural units in the xylylenediamine-based polyamide resin preferably accounts for 90% by mass or more of all structural units, more preferably accounts for 95% by mass or more, even more preferably accounts for 97% by mass or more, and even more preferably accounts for 99% by mass or more.
[0032] It is also preferable to use the thermoplastic resin (particularly polyamide resin, further xylylenediamine-based polyamide resin) produced from recycled resin or biomass raw material (biomass thermoplastic resin). By using biomass thermoplastic resin, it is possible to reduce the environmental load. For example, in xylylenediamine-based polyamide resins, bio-adipic acid can be used as a biomass raw material. Mass balance certified (ISCC PLUS) adipic acid can also be used. Mass balance certification means that the amount of renewable raw materials and bio-raw materials used at each factory or production facility and the amount of products produced or shipped are quantified and guaranteed together with the quality.
[0033] The melting point of the thermoplastic resin (preferably xylylenediamine-based polyamide resin) contained in the continuous thermoplastic resin fiber (1) is preferably 150°C or higher, more preferably 180°C or higher, even more preferably 200°C or higher, and even more preferably 205°C or higher. The melting point of the thermoplastic resin (preferably xylylenediamine-based polyamide resin) is preferably 350°C or lower, more preferably 330°C or lower, even more preferably 300°C or lower, even more preferably 280°C or lower, even more preferably 260°C or lower, and even more preferably 250°C or lower. When the continuous thermoplastic resin fiber (1) of this embodiment contains two or more thermoplastic resins, the melting point of the thermoplastic resin constituting the continuous thermoplastic resin fiber (1) is the melting point of the resin with the highest melting point. The melting point is measured as described in the Examples section below.
[0034] The lower limit of the number average molecular weight (Mn) of the thermoplastic resin (preferably a xylylenediamine-based polyamide resin) is preferably 6,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more, and is preferably 10,000 or less, more preferably 50,000 or less. When the continuous thermoplastic resin fiber (1) used in this embodiment contains two or more kinds of thermoplastic resins, the number average molecular weight is the number average molecular weight of the mixture.
[0035] The number average molecular weight (Mn) of the thermoplastic resin is measured by gel permeation chromatography (GPC) using a standard polymethyl methacrylate (PMMA) equivalent value. Two columns packed with styrene polymers are used as the packing material, and hexafluoroisopropanol (HFIP) with a sodium trifluoroacetate concentration of 2 mmol / L is used as the solvent. The resin concentration is 0.02 mass%, the column temperature is 40°C, the flow rate is 0.3 mL / min, and the measurement is performed using a refractive index detector (RI). In addition, the calibration curve is measured by dissolving six levels of PMMA in HFIP.
[0036] The continuous thermoplastic resin fiber (1) used in this embodiment may contain additives such as antioxidants, stabilizers such as heat stabilizers, hydrolysis resistance improvers, weathering stabilizers, matting agents, ultraviolet absorbers, nucleating agents, plasticizers, dispersants, flame retardants, antistatic agents, coloring inhibitors, gelation inhibitors, colorants, and release agents, within the scope of the objects and effects of the present invention. For details of these, please refer to the descriptions in paragraphs 0130 to 0155 of Japanese Patent No. 4894982 and the descriptions in paragraphs 0047 to 0103 of International Publication No. 2021 / 241471, the contents of which are incorporated herein by reference.
[0037] The proportion of the continuous thermoplastic resin fiber (1) in the composite material of this embodiment is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, even more preferably 25% by mass or more, and even more preferably 30% by mass or more, based on 100% by mass of the composite material. By making the proportion equal to or more than the lower limit, the impregnation time, i.e., the molding time, tends to be shortened. In addition, the proportion of the continuous thermoplastic resin fiber (1) in the composite material of this embodiment is preferably 75% by mass or less, more preferably 70% by mass or less, even more preferably 65% by mass or less, even more preferably 60% by mass or less, and even more preferably 55% by mass or less, based on 100% by mass of the composite material. By making the proportion equal to or less than the upper limit, the carbon ratio in the composite material tends to be increased, and the mechanical properties of the resulting molded product tend to be improved. The composite material of the present embodiment may contain only one type of continuous thermoplastic resin fiber (1), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0038] <Continuous reinforcing fiber with thermosetting resin on the surface (2)> In the composite material of this embodiment, the continuous reinforcing fiber (2) having a thermosetting resin on its surface contains the continuous reinforcing fiber itself and the thermosetting resin, as described above, and typically, the total of the continuous reinforcing fiber itself and the thermosetting resin accounts for 95 mass% (preferably 99 mass% or more and 100 mass% or less) of the total of the continuous reinforcing fiber (2).
[0039] The continuous reinforcing fiber itself in this embodiment refers to a reinforcing fiber having a fiber length of more than 6 mm, preferably more than 12 mm, more preferably more than 30 mm, and even more preferably more than 10 cm. There is no particular restriction on the average fiber length of the continuous reinforcing fiber used in this embodiment, but from the viewpoint of improving molding processability, it is preferably 1 m or more, more preferably 100 m or more, even more preferably 1,000 m or more, and preferably 20,000 m or less, more preferably 1,0000 m or less, and even more preferably 7,000 m or less.
[0040] Examples of the material of the continuous reinforcing fiber itself include inorganic fibers such as glass fiber, carbon fiber, metal fiber, boron fiber, basalt fiber, and ceramic fiber, and organic fibers such as aramid fiber, polyoxymethylene fiber, aromatic polyamide fiber, polyparaphenylene benzobisoxazole fiber, and ultra-high molecular weight polyethylene fiber. Among these, inorganic fibers are preferred from the viewpoint of obtaining high strength, and at least one selected from the group consisting of glass fiber, carbon fiber, and basalt fiber is more preferred because of its light weight, high strength, and high elastic modulus, and carbon fiber is even more preferred. Examples of carbon fibers include polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, etc. Carbon fibers made from plant-derived raw materials such as lignin and cellulose can also be used.
[0041] The continuous reinforcing fiber (2) used in this embodiment has a thermosetting resin on the surface. Examples of the thermosetting resin include epoxy resin, oxetane resin, phenol resin, polyurethane resin, melamine resin, maleimide resin, cyanate resin, etc., and epoxy resin is preferable. In this embodiment, the continuous reinforcing fiber (2) having a thermosetting resin on its surface is preferably a recycled continuous reinforcing fiber, more preferably a recycled continuous carbon fiber, and particularly preferably a recycled reinforcing fiber with a high residual rate of the thermosetting resin.
[0042] In particular, the ratio of the thermosetting resin in the continuous reinforcing fiber (2) is 2% by mass or more, preferably 8% by mass or more, more preferably 10% by mass or more, and may be 12% by mass or more, based on 100% by mass of the continuous reinforcing fiber (2). The ratio of the thermosetting resin in the continuous reinforcing fiber (2) is 40% by mass or less, preferably 38% by mass or less, more preferably 35% by mass or less, and may be 32% by mass or less, based on 100% by mass of the continuous reinforcing fiber (2). By making the ratio equal to or greater than the lower limit, damage to the continuous reinforcing fiber in the obtained molded product can be reduced, and the mechanical strength of the obtained molded product can be further improved. By making the ratio equal to or less than the upper limit, the obtained composite material can be made more flexible. The continuous reinforcing fibers (2) may use one type of thermosetting resin or two or more types. When two or more types are used, the total amount is preferably within the above range.
[0043] The thermosetting resin contained in the continuous reinforcing fiber (2) may be partially carbonized. In particular, when the continuous reinforcing fiber (2) is a recycled product, the proportion of the carbonized resin tends to be high. The content of the thermosetting resin in the reinforcing fiber used in this embodiment means the amount of the thermosetting resin that is not carbonized and remains after carbonization.
[0044] The continuous reinforcing fiber (2) used in this embodiment may be further treated with a treatment agent. Treatment with a treatment agent tends to further improve the degree of integration of the resulting composite material. In this embodiment, it is preferable that at least a part of the treatment agent is present on the surface of the thermosetting resin of the continuous reinforcing fiber (2) having a thermosetting resin on its surface. Furthermore, in this embodiment, it is preferable that at least a part of the treatment agent is present on the surface of the thermosetting resin of the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2) having a thermosetting resin on its surface. The treatment agent is a surface treatment agent and / or a sizing agent.
[0045] Specifically, the treating agent that can be used in the present embodiment is preferably at least one of an epoxy resin, a urethane resin, a silane coupling agent, a water-insoluble nylon, and a water-soluble nylon, more preferably at least one of an epoxy resin, a urethane resin, a water-insoluble nylon, and a water-soluble nylon, and even more preferably a water-soluble nylon.
[0046] Here, water-insoluble nylon means that when 1 g of nylon is added to 100 g of water at 25°C, 99% by mass or more does not dissolve. When using water-insoluble nylon, it is preferable to use a powdered water-insoluble nylon dispersed or suspended in water or an organic solvent. The mixed fiber bundle can be immersed in such a dispersion or suspension of the powdered water-insoluble nylon and then dried to obtain a mixed fiber yarn. Examples of water-insoluble nylon include nylon 6, nylon 66, nylon 610, nylon 11, nylon 12, xylylenediamine-based polyamide resins (preferably polyxylylene adipamide and polyxylylene sebacamide), and copolymer powders thereof emulsified and dispersed with the addition of a nonionic, cationic, anionic surfactant or a mixture thereof. Commercially available water-insoluble nylon products are sold as water-insoluble nylon emulsions, for example, Sepolsion PA manufactured by Sumitomo Seika Chemicals and Michem Emulsion manufactured by Michaelman.
[0047] Here, water-soluble nylon means that when 1 g of nylon is added to 100 g of water at 25° C., 99% or more by mass of it dissolves in water. Examples of the water-soluble nylon include modified polyamides such as acrylic acid grafted N-methoxymethylated nylon, N-methoxymethylated nylon with an amide group, etc. Examples of the water-soluble nylon include commercially available products such as AQ-nylon manufactured by Toray and Toresin manufactured by Nagase ChemteX.
[0048] The amount of the treatment agent is preferably 0.001 to 5 mass %, more preferably 0.1 to 4 mass %, and even more preferably 0.5 to 4 mass %, relative to 100 mass % of the amount of the continuous reinforcing fibers themselves contained in the continuous reinforcing fibers (2).
[0049] The content of the continuous reinforcing fiber (2) in the composite material of this embodiment is more preferably 40 parts by mass or more, more preferably 45 parts by mass or more, even more preferably 50 parts by mass or more, even more preferably 55 parts by mass or more, and may be 60 parts by mass or more, based on 100 parts by mass of the total of the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2). By making it equal to or more than the lower limit, the thermoplastic resin fiber can be arranged all around the reinforcing fiber, and the impregnation time, i.e., the molding time, tends to be shortened. In addition, the content of the continuous reinforcing fiber (2) in the composite material of this embodiment is preferably 90 parts by mass or less, more preferably 85 parts by mass or less, based on 100 parts by mass of the total of the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2). By making it equal to or less than the upper limit, the carbon ratio in the composite material tends to be increased, and the mechanical properties of the obtained molded product tend to be improved. The composite material of the present embodiment may contain only one type of continuous reinforcing fiber (2), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0050] <Thermoplastic resin (3) having a lower melting point than the resin constituting the continuous thermoplastic resin fiber (1)> The composite material of the present embodiment contains a thermoplastic resin (3) (binder resin) having a melting point lower than that of the resin constituting the continuous thermoplastic resin fiber (1). By using such a binder resin, the thermoplastic resin fiber (1) and the continuous reinforcing fiber (2) can be effectively bound. The binder resin is a resin whose main component is a thermoplastic resin having a melting point lower than that of the resin constituting the continuous thermoplastic resin fiber (1) (usually 90% by mass or more, preferably 95% by mass or more, and 100% by mass or less, of 100% by mass of the binder resin), and may further contain known additives, etc. As the thermoplastic resin, a wide variety of known thermoplastic resins can be used, and a crystalline resin is preferable.
[0051] The difference between the melting point of the resin constituting the continuous thermoplastic resin fiber (1) and the melting point of the binder resin is preferably 1°C or more, more preferably 5°C or more, even more preferably 10°C or more, even more preferably 15°C or more, even more preferably 20°C or more, and even more preferably 30°C or more. By making it equal to or more than the lower limit, the thermoplastic resin fiber (1) can more appropriately maintain the fibrous shape, flexibility remains in the composite material, and the design can be beautifully reflected when the preform is produced. In addition, the difference between the melting point of the resin constituting the continuous thermoplastic resin fiber (1) and the melting point of the binder resin is preferably 100°C or less, more preferably 70°C or less, even more preferably 60°C or less, even more preferably 50°C or less, and even more preferably 49°C or less. By making it equal to or less than the upper limit, the thermal deterioration of the thermoplastic resin fiber (1) can be effectively suppressed. When the composite material of the present embodiment contains two or more binder resins, the melting point of the binder resin having the higher melting point is regarded as the melting point. The melting point is measured as described in the Examples section below.
[0052] Examples of the thermoplastic resin used for the binder resin include polyolefin resins such as polyethylene and polypropylene; polyester resins such as polyamide resin, polyethylene terephthalate and polybutylene terephthalate; polyether ketone resins such as polyoxymethylene resin, polyether ketone, polyether ether ketone, polyether ketone ketone and polyether ether ketone ketone; thermoplastic polyimide resins such as polyether sulfone resin, polyether sulfide resin, thermoplastic polyether imide, thermoplastic polyamide imide, wholly aromatic polyimide and semi-aromatic polyimide; and the like. Polyamide resin is more preferable. The polyamide resin used in this embodiment may be either an aliphatic polyamide resin or an aromatic polyamide resin. Examples of the aliphatic polyamide resin and the aromatic polyamide resin are the same as those described above in the section on the continuous thermoplastic resin fiber (1), except for the following.
[0053] The binder resin is preferably a xylylenediamine-based polyamide resin. The xylylenediamine-based polyamide resin in this embodiment is a polyamide resin that contains diamine constituent units and dicarboxylic acid constituent units, and in which 70 mol % or more of the diamine constituent units are derived from xylylenediamine. Preferably, the xylylenediamine-based polyamide resin has 50 mol % or more of the dicarboxylic acid constituent units derived from an α,ω-linear aliphatic dicarboxylic acid having a carbon number of 4 to 20. In the composite material of the present embodiment, the strength and chemical resistance inherent to the xylylenediamine-based polyamide resin can be exhibited.
[0054] In the binder resin, the molar ratio of metaxylylenediamine to paraxylylenediamine in xylylenediamine, when the total of metaxylylenediamine and paraxylylenediamine is 100 moles, is preferably metaxylylenediamine / paraxylylenediamine, from 0 to 100 / 100 to 0, and more preferably 10 to 100 / 90 to 0. By including metaxylylenediamine, the melting point of the polyamide resin can be lowered. Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are suitable for use as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid. One or more of these can be used in combination, and among these, one or more of adipic acid, sebacic acid, and dodecanedioic acid are more preferred, with adipic acid and / or sebacic acid being more preferred. A preferred embodiment of the xylylenediamine-based polyamide resin in the binder resin is one in which 50 mol % or more (preferably 70 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid constituent units are derived from one or more of adipic acid, sebacic acid, and dodecanedioic acid (preferably adipic acid and / or sebacic acid, more preferably adipic acid).
[0055] The melting point of the thermoplastic resin (preferably a xylylenediamine-based polyamide resin) contained in the binder resin is preferably 120° C. or higher, more preferably 130° C. or higher, even more preferably 150° C. or higher, and even more preferably 180° C. or higher. The melting point of the thermoplastic resin (preferably a xylylenediamine-based polyamide resin) is preferably 300° C. or lower, more preferably 250° C. or lower, even more preferably 220° C. or lower, and even more preferably 200° C. or lower.
[0056] The binder resin used in this embodiment may contain additives such as antioxidants, stabilizers such as heat stabilizers, hydrolysis resistance improvers, weathering stabilizers, matting agents, UV absorbers, nucleating agents, plasticizers, dispersants, flame retardants, antistatic agents, coloring inhibitors, gelling inhibitors, colorants, and release agents, within the scope of the purpose and effect of the present invention. For details of these, please refer to the descriptions in paragraphs 0130 to 0155 of Japanese Patent No. 4894982 and the descriptions in paragraphs 0047 to 0103 of International Publication No. 2021 / 241471, the contents of which are incorporated herein by reference.
[0057] The content of the binder resin in the composite material of this embodiment is 5 parts by mass or more, preferably 10 parts by mass or more, and more preferably 15 parts by mass or more, relative to 100 parts by mass of the total of the continuous thermoplastic resin fiber (1) and the binder resin. By making the content equal to or more than the lower limit, the continuous thermoplastic resin fiber (1) can be bonded to the continuous reinforcing fiber (2) through the binder without leakage. In addition, the content of the binder resin in the composite material of this embodiment is 80 parts by mass or less, preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 55 parts by mass or less, relative to 100 parts by mass of the total of the continuous thermoplastic resin fiber (1) and the binder resin. By making the content equal to or less than the upper limit, flexibility remains in the composite material, and the design tends to be more beautifully reflected when the molded product is produced. The composite material of the present embodiment may contain only one type of binder resin, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0058] In the present embodiment, it is preferable that the resin constituting the continuous thermoplastic resin fibers (1) and the binder resin each independently contain a polyamide resin, and it is preferable that each independently contain a xylylenediamine-based polyamide resin.
[0059] <Method of manufacturing composite materials> The composite material of this embodiment can be produced by a known method, for example, by binding the opened continuous thermoplastic resin fibers (3) and the continuous reinforcing fibers (2) having a thermosetting resin on the surface (preferably recycled carbon fibers with the thermosetting resin remaining thereon) with a binder resin to produce a composite material. It is preferable to heat during binding, and the heating temperature at this time is preferably the melting point of the binder resin minus 10°C or more, more preferably the melting point of the binder resin minus 5°C or more, even more preferably the melting point of the binder resin or more, still more preferably the melting point of the binder resin + 5°C or more, and preferably the melting point of the thermoplastic resin constituting the thermoplastic resin fiber (1) + 5°C or less, more preferably less than the melting point of the thermoplastic resin constituting the thermoplastic resin fiber (1), even more preferably the melting point of the thermoplastic resin constituting the thermoplastic resin fiber (1) - 5°C or less, and even more preferably the melting point of the thermoplastic resin constituting the thermoplastic resin fiber (1) - 10°C or less. By heating at such a temperature, the fibrous shape of the continuous thermoplastic resin fibers (1) is easily maintained, the resulting composite material becomes flexible, and the degree of integration with the continuous reinforcing fibers (2) is further improved. EXAMPLES
[0060] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0061] 1.Raw materials <Continuous reinforcing fiber (2)> CF1: Recycled carbon fiber roving, type of curable resin: epoxy resin, proportion of remaining thermosetting resin that has not become carbonized after carbonization: 10% by mass CF2: Recycled carbon fiber roving, type of curable resin: epoxy resin, proportion of remaining thermosetting resin that has not become carbonized after carbonization: 30% by mass CF3: Recycled carbon fiber roving, type of curable resin: acrylate resin, proportion of remaining thermosetting resin that has not become carbonized after carbonization: 10% by mass The recycled carbon fibers used were all carbonized at 500°C for two hours.
[0062] <Thermoplastic resin> MPXD10: Polyamide resin synthesized in Synthesis Example 1 MXD6: Polyamide resin synthesized from adipic acid and metaxylylenediamine, manufactured by Mitsubishi Gas Chemical Company, #6007 MPXD12: Polyamide resin synthesized from metaxylylenediamine, paraxylylenediamine (MP ratio: 7:3) and dodecanedioic acid N66: Polyamide 66, Toray, Amilan CM3001 MXD10: Polyamide resin synthesized in Synthesis Example 3 N12: Polyamide 12, manufactured by Ube Industries, UBESTA PET: Polyethylene terephthalate resin, Invista, 1101E, inherent viscosity 0.80 dL / g
[0063] <Surface treatment agent> Water-soluble nylon: Toray AQ nylon T70 Epoxy: Adeka EM-058
[0064] <Synthesis Example 1: Synthesis of MPXD10> Sebacic acid (manufactured by CASDA) was placed in a jacketed reactor equipped with a stirrer, a partial condenser, a cooler, a thermometer, a dropping tank and a nitrogen gas inlet tube, and the contents were thoroughly replaced with nitrogen. After heating and melting at 170°C, a mixed amine (70:30) of metaxylylenediamine and paraxylylenediamine (manufactured by Mitsubishi Gas Chemical Company, MPXDA) was gradually dropped so that the molar ratio with sebacic acid was 1:1 while stirring the contents, and the temperature was raised to 240°C. After the dropwise addition was completed, the temperature was raised to 260°C and continued for 20 minutes. Thereafter, the pressure inside the reaction system was continuously reduced to 0.08 MPa, and the reaction was continued. After the reaction was completed, a pressure of 0.2 MPa was applied to the inside of the reactor with nitrogen gas, and the polymer was taken out as a strand from a nozzle at the bottom of the polymerization tank, cooled with water, and pelletized with a pelletizer to obtain the polymer.
[0065] <Synthesis Example 2: Synthesis Example of MPXD12> In a reaction vessel equipped with a stirrer, partial condenser, cooler, thermometer, dropping device, nitrogen inlet tube, and strand die, 13,820g (60mol) of dodecanedioic acid and 15.43g of sodium acetate / sodium hypophosphite monohydrate (molar ratio = 1 / 1.5) were charged, and 8,173g (60mol, Mitsubishi Gas Chemical Co., Ltd.) of a mixed diamine with a ratio of metaxylylenediamine and paraxylylenediamine of 70:30 was dropped into the reaction vessel with stirring, and the internal temperature was continuously raised to 240°C over 2.5 hours while removing the generated condensation water into the system. After the dropping was completed, the internal temperature was raised, and when it reached 250°C, the pressure in the reaction vessel was reduced, and the internal temperature was further raised to 255°C for 20 minutes to continue the melt polycondensation reaction. Thereafter, the system was pressurized with nitrogen, and the polymer was taken out from the strand die and pelletized to obtain polyamide resin MPXD12.
[0066] <Synthesis Example 3: Synthesis of MXD10> Sebacic acid (manufactured by CASDA) was placed in a jacketed reactor equipped with a stirrer, a partial condenser, a cooler, a thermometer, a dropping tank and a nitrogen gas inlet tube, and the contents were thoroughly replaced with nitrogen. After heating and melting at 170°C, metaxylylenediamine (manufactured by Mitsubishi Gas Chemical Co., Ltd., MXDA) was gradually dropped so that the molar ratio with sebacic acid was 1:1 while stirring the contents, and the temperature was raised to 240°C. After the dropwise addition was completed, the temperature was raised to 260°C and continued for 20 minutes. Thereafter, the pressure inside the reaction system was continuously reduced to 0.08 MPa, and the reaction was continued. After the reaction was completed, the inside of the reactor was pressurized with 0.2 MPa of nitrogen gas, and the polymer was taken out as a strand from a nozzle at the bottom of the polymerization tank, cooled with water, and pelletized with a pelletizer to obtain the polymer.
[0067] <Method for measuring the proportion (mass%) of thermosetting resin in continuous reinforcing fiber (2)> Ten continuous reinforcing fibers (2) of 1 meter each were cut from the roving, their masses were measured, and the masses were multiplied by 1000 to obtain the fineness (number of grams per 1000 m). The fineness was calculated from the ratio of the masses to the fineness (number of grams per 1000 m) of virgin carbon fibers.
[0068] <Method for producing continuous thermoplastic resin fiber (1) and continuous thermoplastic resin fiber (3) (binder resin)> The thermoplastic resin was melt extruded using a single screw extruder having a 30 mmφ screw, extruded in the form of a strand from a die with 48 holes, and stretched while being wound around a roll to obtain a continuous thermoplastic resin fiber bundle wound around a roll.
[0069] <Measuring method for melting point of thermoplastic resin> The melting point (Tm) was measured by differential scanning calorimetry (DSC) in accordance with ISO11357. Using a differential scanning calorimeter, the resin was placed in the measurement pan of the differential scanning calorimeter, heated to a temperature above the melting point at a rate of 10°C / min under a nitrogen atmosphere, and then rapidly cooled before measurement. The measurement conditions were a heating rate of 10°C / min, held at 280°C for 5 minutes, and then cooled down to 100°C at a rate of -5°C / min to determine the melting point (Tm). The differential scanning calorimeter used was "DSC-60" manufactured by SHIMADZU CORPORATION.
[0070] 2. Examples 1, 2, 5 to 9, Comparative Examples 1 to 3 <Method of manufacturing composite materials> From a continuous thermoplastic resin fiber (1) wound with 1 m or more of thermoplastic resin fiber, a continuous reinforcing fiber (2) wound with 1 m or more of reinforcing fiber, and a continuous thermoplastic resin fiber (3) wound with 1 m or more of thermoplastic resin fiber, the continuous thermoplastic resin fiber (1), the continuous reinforcing fiber (2), and the continuous thermoplastic resin fiber (3) were each drawn out, passed through multiple guides, and spread by blowing air. While spreading, the continuous thermoplastic resin fiber (1), the continuous reinforcing fiber (2), and the continuous thermoplastic resin fiber (3) were bundled, passed through multiple guides, blown with air, and homogenized. The fibers were heated at a temperature at which only the continuous thermoplastic resin fiber (3) melted (melting point of the binder resin constituting the continuous thermoplastic resin fiber (3) + 10°C), and a composite material (hybrid tape, width 9 mm, thickness 0.22 mm) was obtained. The obtained composite material was evaluated according to "4. Evaluation" described below.
[0071] <Production of molded products> The composite material was sewn together in the same direction using the TFP method to produce a preform. The produced preform was placed in a mold heated to the melting point of the continuous thermoplastic resin fiber (1) + 30°C, and press molding was performed using a 100 ton press. After pressing, water was poured into the mold to cool it to 80°C, and then the mold was opened and removed to obtain a molded product. The temperature of the mold during pressing was the melting point of the continuous thermoplastic resin fiber (1) + 30°C, and the pressure was 100 kgf / cm. 2 (9.8 MPa), pressing time 10 minutes, and cooling time 20 minutes. The obtained molded articles were evaluated according to "4. Evaluation" described below.
[0072] 3. Examples 3 and 4 From a continuous thermoplastic resin fiber (1) wound with 1 m or more of thermoplastic resin fiber, a continuous reinforcing fiber (2) wound with 1 m or more of reinforcing fiber, and a continuous thermoplastic resin fiber (3) wound with 1 m or more of thermoplastic resin fiber, the continuous thermoplastic resin fiber (1), the continuous reinforcing fiber (2), and the continuous thermoplastic resin fiber (3) were each drawn out, passed through multiple guides, and spread by air blowing. While spreading, the continuous thermoplastic resin fiber (1), the continuous reinforcing fiber (2), and the continuous thermoplastic resin fiber (3) were bundled, passed through multiple guides, and air blown to promote homogenization. The fibers were heated at a temperature at which only the continuous thermoplastic resin fiber (3) melted (melting point of the binder resin constituting the continuous thermoplastic resin fiber (3) + 10°C), and a hybrid tape (width 9 mm, thickness 0.22 mm) was obtained. The obtained hybrid tape was immersed in an aqueous solution containing a surface treatment agent for 10 seconds, and then dried at 40°C for 60 minutes if the surface treatment agent was water-soluble nylon, or at 60°C for 45 minutes if the surface treatment agent was epoxy, to obtain a composite material. The obtained composite material was evaluated according to "4. Evaluation" described below.
[0073] <Production of molded products> By the TFP method, the composite material was stitched in the same direction to produce a preform. The produced preform was placed in a mold heated to the melting point of the continuous thermoplastic resin fiber (1) + 30 °C, and press molding was performed using a 100 t press machine. After pressing, water was poured into the mold and cooled to 80 °C, then the mold was opened and taken out to obtain a molded product. The temperature of the mold during pressing was the melting point of the continuous thermoplastic resin fiber (1) + 30 °C, the pressure was 100 kgf / cm 2 (9.8 MPa), the pressing time was 10 minutes, and the cooling time was 20 minutes. The obtained molded product was evaluated according to "4. Evaluation" described below.
[0074] 4. Evaluation <Degree of integration> The degree of integration of the composite material was evaluated as follows. The composite material was cut into 10 cm pieces, and one end was fixed with gum tape. Then, holding the 1 cm part at the opposite end by hand, it was brought closer to the end fixed with gum tape at a speed of 1 cm / min so that the surface of the composite material was in contact. The evaluation was carried out by 5 experts and judged by a majority vote. S: When approaching with the end-through, even when both ends came into contact, they did not disperse and were integrated. A: When approaching with the end-through, when both ends approached 8 cm, a part dispersed. B: When approaching with the end-through, when both ends approached 5 cm, a part dispersed. C: When approaching with the end-through, when both ends approached 3 cm, a part dispersed. For Examples 1 to 9 and Comparative Examples 1 and 2 that were integrated, the following evaluations were carried out.
[0075] <TFP workability (flexibility)> The TFP workability (flexibility) of the composite material was evaluated as follows. The composite material was pierced in a spiral circular pattern using a TFP device (manufactured by TISM Co., Ltd., product number: TCWM-T01). The piercing speed was 500 rpm. The evaluation was carried out by 5 experts and judged by a majority vote. A: When piercing with the TFP device, the intended piercing was achieved B: Other than A above, when embroidering with a TFP device, some parts deviated from the intended path, but the embroidery was generally completed as intended. An example of the above-mentioned evaluation A is shown in FIG. 4(1), and an example of the above-mentioned evaluation B is shown in FIGS. 4(2) and (3).
[0076] <Rate of fiber loss from composite material> Two bobbins of the same shape and mass were prepared, and the composite material obtained was wound on one of the bobbins and then transferred to the other bobbin. The winding speed was 10 m / min. Evaluation was performed as follows. A: The mass after winding is 98% or more of the mass before winding B: The mass after winding is 95% or more and less than 98% of the mass before winding C: The mass after winding is less than 95% of the mass before winding
[0077] <Flexural strength and flexural modulus> The molded product obtained above was cut to a size suitable for the standard using a Makita sliding circular saw, and the process was carried out in accordance with JIS K7074. The units of bending strength and bending modulus were MPa. Moreover, no measurement was performed for Comparative Examples 1 to 3, which could not be molded by TFP.
[0078] [Table 1]
[0079] [Table 2]
[0080] [Table 3]
[0081] As is clear from the above results, the composite material of the present invention had excellent integration and TFP workability. Furthermore, the fiber loss rate was low. Furthermore, the molded products made from the composite material of the present invention had excellent mechanical strength (Examples 1 to 9). In contrast, when the melting point of the resin constituting the continuous thermoplastic resin fiber (1) was the same as or lower than the melting point of the binder resin (thermoplastic resin (3)) (Comparative Examples 1 and 2), the fiber lacked flexibility and TFP was not possible. Moreover, when the amount of the thermosetting resin contained in the continuous reinforcing fibers (2) was large (Comparative Example 3), the fibers were not in a fibrous form and TFP was not possible. [Explanation of symbols]
[0082] 1. Continuous thermoplastic resin fibers (2) 2. Continuous reinforcing fiber itself 3. Binder resin 4 Thermosetting resin 10 Composite materials 11. Thread
Claims
1. Continuous thermoplastic resin fibers (1); A continuous reinforcing fiber (2) having a thermosetting resin on its surface; A composite material having a thermoplastic resin (3) having a melting point lower than that of a resin constituting the continuous thermoplastic resin fiber (1), The continuous reinforcing fibers (2) contain the thermosetting resin in a ratio of 2 to 40 mass%, The content of the thermoplastic resin (3) in the composite material is 5 to 80 parts by mass per 100 parts by mass of the total of the continuous thermoplastic resin fibers (1) and the thermoplastic resin (3), At least a part of the continuous thermoplastic resin fibers (1) and at least a part of the continuous reinforcing fibers (2) are bound via the thermoplastic resin (3). Composite material.
2. 2. The composite material of claim 1, wherein the continuous reinforcing fibers (2) comprise recycled continuous reinforcing fibers.
3. 3. The composite material according to claim 1 or 2, wherein the continuous reinforcing fibers (2) comprise recycled continuous carbon fibers.
4. The composite material according to any one of claims 1 to 3, wherein the continuous thermoplastic resin fibers (1) and the thermoplastic resin (3) each independently comprise a polyamide resin.
5. The composite material according to any one of claims 1 to 4, wherein the resin constituting the continuous thermoplastic resin fibers (1) contains a xylylenediamine-based polyamide resin that contains diamine constituent units and dicarboxylic acid constituent units, and 70 mol% or more of the diamine constituent units are derived from xylylenediamine.
6. The composite material according to any one of claims 1 to 5, wherein the thermoplastic resin (3) contains a xylylenediamine-based polyamide resin containing diamine constituent units and dicarboxylic acid constituent units, and 70 mol% or more of the diamine constituent units are derived from xylylenediamine.
7. 7. The composite material according to claim 5, wherein 50 mol % or more of the dicarboxylic acid constituent units in the xylylenediamine-based polyamide resin are constituent units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms.
8. a continuous thermoplastic resin fiber layer in which the continuous thermoplastic resin fibers (1) are arranged in parallel in one direction; The continuous reinforcing fiber layer has the continuous reinforcing fibers (2) arranged in parallel in one direction, The composite material according to any one of claims 1 to 7, wherein the thermoplastic resin (3) binds the continuous thermoplastic resin fiber layer and the continuous reinforcing fiber layer.
9. The composite material according to claim 8, wherein the continuous thermoplastic resin fibers (1) and the continuous reinforcing fibers (2) are arranged in parallel in the same direction.
10. The composite material according to any one of claims 1 to 9, wherein the continuous reinforcing fiber (2) is contained in an amount of 40 to 90 parts by mass per 100 parts by mass of the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2).
11. The composite material according to any one of claims 1 to 10, which is in the form of a tape.
12. The composite material according to any one of claims 1 to 11, which is for Tailored Fiber Placement processing.
13. The continuous reinforcing fiber (2) is a recycled carbon fiber, the continuous thermoplastic resin fiber (1) and the thermoplastic resin (3) each independently contain a diamine constituent unit and a dicarboxylic acid constituent unit, and contain a xylylenediamine-based polyamide resin in which 70 mol % or more of the diamine constituent units are derived from xylylenediamine; 50 mol % or more of the dicarboxylic acid constituent units in the xylylenediamine-based polyamide resin are derived from α,ω-linear aliphatic dicarboxylic acid constituent units having 4 to 20 carbon atoms, a continuous thermoplastic resin fiber layer in which the continuous thermoplastic resin fibers (1) are arranged in parallel in one direction; The continuous reinforcing fiber layer has the continuous reinforcing fibers (2) arranged in parallel in one direction, The thermoplastic resin (3) binds the continuous thermoplastic resin fiber layer and the continuous reinforcing fiber layer, The continuous thermoplastic resin fibers (1) and the continuous reinforcing fibers (2) are arranged in the same direction, The continuous reinforcing fiber (2) is contained in an amount of 40 to 90 parts by mass relative to a total of 100 parts by mass of the continuous thermoplastic resin fiber (1) and the continuous reinforcing fiber (2), It is in tape form, The composite material according to any one of claims 1 to 12, which is for Tailored Fiber Placement processing.
14. A molded article formed from the composite material according to any one of claims 1 to 13.
15. A method for producing a molded article, comprising stitching the composite material according to any one of claims 1 to 13 to a substrate and performing a tailored fiber placement process.
Citation Information
Patent Citations
Mixed yarn, woven fabric and knitted fabric, composite material and method for manufacturing composite material
JP2014173196A
Combined filament yarn and manufacturing method thereof, braid, cloth, knitting and non-woven fabric
JP2015098669A